Intact Cell Binding for In Vitro Prediction of Sedative and Non-sedative Histamine H1-Receptor Antagonists Based on Receptor Internalization - Shigeru Hishinuma; Yuko Sato; Yusuke Kobayashi; Hiroshi Komazaki; Masaki Saito (Elsevier, 2008)
We evaluated changes in the binding properties of sedative and non-sedative histamine H1-receptor antagonists induced by internalization of H1 receptors in intact human U373 MG astrocytoma cells. Internalization of H1 receptors was induced without their degradation by treatment with 0.1 mM histamine for 30 min at 37°C, and then the intact cell binding assay was performed at 4°C. The binding properties of [3H]mepyramine, a cell-penetrating radioligand for H1 receptors, were not changed by histamine pretreatment. Displacement curves for sedative H1-receptor antagonists (diphenhydramine, chlorpheniramine, promethazine, ketotifen, azelastine and oxatomide) against [3H]mepyramine binding were not changed by histamine pretreatment. In contrast, the displacement curves for non-sedative H1-receptor antagonists (mequitazine, bepotastine, olopatadine, epinastine, carebastine, desloratadine and fexofenadine) were changed by histamine pretreatment: two types of changes, i.e. a rightward shift in the monophasic curve or an increase in the proportion of the low affinity component of the biphasic curve, were prevented under hypertonic conditions, in which clathrin-mediated receptor internalization is known to be inhibited. Thus, internalization-mediated changes in the binding properties of H1-receptor antagonists were well correlated with their sedative and nonsedative behaviors, which might confirm their permeability through the biomembrane and possibly the blood brain barrier. Keywords:: histamine H1 receptor, intact cell binding, membrane permeability, receptor internalization, sedative and non-sedative antihistamines